Synthesis, spectral, MOE and cytotoxic studies of nano Ru (III), Pr (III) and Gd (III) metal complexes with new Schiff base ligand based on dibenzoyl methane and anthranilic acid. (22nd May 2020) - Mahmoud, Nessma F.; Mahmoud, Walaa H.; Mohamed, Gehad G.
Abstract : Three metal complexes of Gd (III), Pr (III) and Ru (III) metal ions with Schiff base ligand (H2 L) (prepared through l:2 condensation of dibenzoyl methane and anthranilic acid) were prepared and characterized using various physio‐chemical methods like: elemental analyses, IR, mass spectrometry, magnetic moment, 1 H NMR, SEM and TG/DTG thermal analysis. The analytical and spectroscopic tools showed that the complexes had composition of ML type with octahedral geometry. The mass spectra gave the possible molecular ion peaks of the Schiff base ligand and three metal chelates. The 1 H NMR data supported the IR finding that the ligand coordinated to the metal ions via carboxylate proton displacement. Thermal analysis (TG/DTG) was utilized to differentiate between coordinated and hydrated water molecules. The Schiff base (H2 L) and its metal complexes have been screened for their antibacterial activity against Gram (+) bacteria ( Streptococcus aureus and Bacillis subtilis ), Gram (−) bacteria ( Salmonella typhimurium and Escherichia coli ) and two fungi ( Aspergillus fumigatu and Candida albicans ) organisms by agar diffusion method. The anticancer activity was screened against human breast cancer cell line (MCF‐7). The H2 L ligand and its metal chelates were docked using MOE 2008 software with crystal structure of Gram (+) bacteria: Staphylococcus aureus (PDB ID: 3Q8U) and Gram (−) bacteria: Salmonella typhimurium (PDB ID: lDZR) to identify the binding orientation or conformation of the complex in the active site of the protein. Abstract : Schiff base ligand, H2 L and its three new lanthanide metal complexes were prepared and characterized using different tools. Molecular docking studies of the free Schiff base ligand and Ru (III) complex with receptors of different proteins reveal Ru (III) complex show highest binding ability and the minimum biding energy. The results of anticancer assay of ligand and the complexes suggested the Ru (III) complex exhibited the lowest IC50 was more effective against breast cancer cell line.